A pilot study on the preventative potential of alpha-cyclodextrin and hydroxytyrosol against SARS-CoV-2 transmission - Ergoren, Mahmut Cerkez (Acta Biomed, 2020)
BACKGROUND AND AIM OF THE WORK: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current pandemics of coronavirus disease. This virus is able to attack the cells of the airway epithelium by binding to the transmembrane angiotensin I converting enzyme 2 (ACE2). In the current study, we experimented a food supplement containing alpha-cyclodextrin and hydroxytyrosol as active compounds for the improvement of the defenses against the SARS-CoV-2. Hydroxytyrosol has anti-viral properties and is able to reduce the serum lipids in mice fed with high-cholesterol diet, and α-cyclodextrin has the ability to deplete sphingolipids and phospholipids from the cellular membranes. The aim of the present preliminary open non-controlled interventional study was to evaluate the efficacy of alpha-cyclodextrin and hydroxytyrosol in improving defenses against SARS-CoV-2. METHODS: Fifty healthy volunteers at a higher risk of SARS-CoV-2 infection from Northern Cyprus and six positive individuals for SARS-CoV-2 by RT-qPCR assay were enrolled in this study. The in silico prediction analysis was performed using the bioinformatic tool D3DOCKING to evaluate the interactions of hydroxytyrosol and alpha-cyclodextrin with proteins involved in the biological cycle of SARS-CoV-2 in the humans. RESULTS: The 50 volunteers did not become positive in 15 days for SARS-CoV-2 RT-qPCR assay after the administration of the compound for two weeks, despite they were at higher risk of infection than the general population. Interestingly, in the cohort of six positive patients, two patients were administered with the spray and became negative after five days of spray administration, despite the viral load was higher in the treated subjects than the patients that did not take the compound and that became negative after ten days. In addition, we have identified the presence of possible direct interactions among hydroxytyrosol and alpha-cyclodextrin with the viral protein Spike and the human proteins ACE2 and TMPRSS2. CONCLUSIONS: We preliminary reported on the results of the possible role of alpha-cyclodextrin and hydroxytyrosol in improving defenses against SARS-CoV-2. The next step would be the administration of the compound on a larger cohort in a controlled study and see whether there is a reduced infection rate of SARS-CoV-2 in the treated subjects than in the non-treated individuals. (www.actabiomedica.it)